ASSESSING THE VALIDITY AND RELIABILITY OF ADAPTED CLASSROOM CLIMATES INSTRUMENT FOR MALAYSIAN RURAL SCHOOLS USING PLS-SEM - Priscilla Petrus Dolinting; Vincent Pang, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The association between classroom climate qualitity and studentsâ€™ academic achievement has been well researched. The relationship of a student to the classroom climate can be viewed from the seminal work of Moos (1974) in classifying the dimensions between individual relationship and the surrounding environment into â€œrelationshipâ€, â€œpersonal growthâ€ as well as â€œsystems maintenance and changeâ€. Studentsâ€™ perspective on their classroom climate can be used as a mechanism for classroom assessment to provide useful information regarding the strengths and weaknesses as well as an opportunity for teacherâ€™s reflection in teaching practices. Hence, the main objective of this study is to produce empirical evidence of the validity and reliability of the item in Malay version of What is Happening in This Class? (WIHIC) questionnaire in the context of Malaysian rural secondary schools which is used to study studentsâ€™ perceptions of their mathematics learning experiences in the classroom. PLS-SEM approach with aided by Smart PLS version 3.2.8 software was used to examine the internal consistency reliability, convergent validity, discriminant validity. The translated questionnaire was administered to 338 students of rural secondary schools in Sabah, Malaysia by using the multi-stage cluster sampling. Results showed a PLS-SEM measurement model with 48-items demonstrating good convergent and discriminant validity and reliability. This finding concluded that all items in the Malay version of WIHIC are valid and reliable to be used in future study. Lastly, the current study supports the use of WIHIC for educational practices improvement that could be beneficial to stakeholders such as teachers, administrators and policy makers.